Investigating The Possibility of Extracting Phenolic Compounds from Raisin Waste with The Aim of Waste Management from Raisin Processing Units - Amir Abbas Matin; Bahar Azimi; Hosein Hashempoor (محیط زیست و توسعه فرابخشی)
Introduction: Grapes are one of the most important and most productive agricultural harvests in the world. Iran is currently the seventh largest producer of grapes in the world, with over 252,000 hectares of vineyards. Also, due to its fertile lands, Iran has been known since ancient times for its diversity in grape varieties and the production and export of various types of its products.Given the economic importance of raisins and grapes in the national economy and the country's great potential for improving the quantity and quality of this group of products, and given the global competition in the agricultural market and the high potential of the raisin product for export, the need to produce this product is obvious. One of the important factors for survival in today's competitive condition, is reducing the costs of production and marketing the product. Choosing the right methods can significantly reduce costs and increase the competitiveness of manufacturers. The existence of inseparable waste in this industry has faced producers with challenges that, if waste and scrap management during processing is carried out with the help of modern technology, it will be of great help to producers not only in terms of waste disposal but also in terms of energy and cost savings. In the field of raisins, the added value of by-products resulting from waste, which is currently achieved in leading countries, is sometimes equal to the product itself. Raisin waste is recycled and used in various ways. One of the valuable compounds in grapes is phenolic compounds that are used in various industries. In this work, with the aim of management of raisin production units’ waste, the potential of various raisin wastes in extracting phenolic compounds has been investigated.Materials and Methods: To investigate the possibility of extracting phenolic compounds from raisin waste from raisin processing units in East Azerbaijan province, various raisin wastes including laser-backed wastes, empty, tail chips, broken and immature wastes were investigated for the extraction of phenolic compounds. Also, various solvents including methanol, ethanol, acetone and combinations of solvents were used to extract phenolic compounds. The parameters of extraction efficiency, antioxidant activity and total phenol content were used to evaluate and compare the process. To measure the antioxidant property, the DPPH free radical scavenging method and to calculate the total phenol content, the Folin reagent reaction method was used.Results: The results showed that all raisin wastes contained phenolic compounds in different amounts. The amount of antioxidant activity for unripe raisin, fractured, tail, absurd, and laser were ontained as 23.16, 24.31,26.19,28.42, and 18.82 µg/ml respectively. Also, the phenolic content for unripe raisin, fractured, tail, absurd, and laser were ontained as 421, 426.11, 387.86, 369.24, and 465.2 mg GAE/100 g respectively. Among the raisin waste, the laser waste has the best condition in terms of phenol content and antioxidant activity. Also, the best solvent for extracting phenolic compounds is pure methanol. Laser waste in the extraction solvent of pure methanol has 468.2 mg per gram of gallic acid equivalent extract with phenolic content.Discussion: Based on results, it is concluded that, the best antioxidant result obtained at the lowest IC50 value is related to laser waste with a concentration of 18.82 μg/ml. In general, the results showed that raisin processing waste can be used as a costeffective source for extracting phenolic compounds.